Selected physico-chemical and biological properties of soils in different farming systems - Qatyan, Abrar Saleh Maqtan Ba (2019)
Climate change, loss of fertile top soil, unsustainable agriculture practices and excessive use of agrochemicals lead to soil depletion, loss of agriculture land and threat to food security. These problems cannot be ignored and sustainable solutions must be found to ensure human existence. In the past, the agronomist and soil scientist devoted primarily on soil physical and chemical properties to address some of those issues. Recently, the issues of soil health are beginning to be taken seriously. Therefore, the objectives of the present study are to characterize the physical and chemical properties of different agriculture land (CEFS, Papaya, Organic and Nilai farm), documenting the soil invertebrates, bacteria and fungi population in those areas. Three composite soil samples were collected from each site, followed by the physical and chemical analysis. The physical properties assessed include soil texture, bulk density, moisture, temperature, and soil porosity. The soil chemical properties were pH, EC, total C&N, C/N, extractable P, Ca, Mg, K, Na, organic matter, and effective CEC. Pitfall traps and Tullgren funnel were used for sampling soil invertebrates. Invertebrates were preserved in 70% ethanol and identified using soil invertebrate morphological classification. The fungi and bacteria were isolated using soil dilution technique and soil plate technique on RBA, PDA and NA. Morphological characteristics of the bacteria and fungi were identified. In addition, API20E biochemical test kit was used to identify bacteria to genus level. The physical and chemical properties of soil showed some variation in each location. CEFS, Papaya and Organic farm in UPM campus have Serdang soil series while Nilai agriculture field has Rengam series. Bulk density ranged between 1.07-1.35 g/cm3, porosity (54.67-65.00), temperature (33.66-38.00 0C), moisture (18.57-32.85%), clay (21.57-39.46%), silt (5.78-22.29%), sand (33.27-56.86) and soil texture class ranged from clay, sandy clay to sandy-clay-loam. Macrofauna were dominant in Papaya and CEFS comprising of about 80% fauna found. Mesofauna comprised of 43.22% in Organic farm, while microfauna composed only 2.85% in Organic farm. The ecosystem engineers comprised of 39.56% in Papaya farm. Litters transformers were highest in CEFS comprising of 54.05% and predatory fauna were highest in Nilai farm comprising of 46.29%. The most common bacteria in all farms were Coccobacillus (31.10%), Bacilli G- comprising (26.91%) in CEFS, Papaya and Organic farm, and Actinobacteria comprising (15.86%) in CEFS, Papaya and Nilai farm respectively. Aspergillus, Penicillium and Trichoderma were the most common fungi in all farms and Ascomycota being the most dominant fungal division comprising of 79.03%. The highest diversity of soil fauna and flora were in Organic farm and CEFS. The overall scores approach enabled the soils to be assessed simultaneously for physical, chemical, invertebrates, bacterial and fungal aspect. It was found that CEFS and Organic farm were superior in overall aspect. This study concluded that undisturbed and organic farm have better overall soil properties than varying level of disturbed soil. The rank and score approach enable the soil with multiple parameter assessment such as physical, chemical, and biological properties to be compared simultaneously.